The The effect of bank health level on stock prices with company size as a variabel control on banking companies listed on Indonesia stock exchange (2013 -2019 period) - Kiki Sonia Putri Kiki Sonia Putri; Erni Masdupi (Financial Management Studies, 2022)
This study aims to analyze the soundness of banks as represented by credit risk, liquidity risk, market risk, good corporate governance, earnings and capital on stock prices in banking companies listed on the Indonesia stock exchange in 2013-2019. This study uses firm size as a control variable. The population in this study are banking companies listed on the Indonesia stock exchange. While the sample in this study was determined by purposive sampling method, in order to obtain 231 samples of banks. However, the final sample of this study was 213 because there were data outliers. The type of data used in this study is secondary data obtained from the Indonesia stock exchange website and the official website of each bank. The analytical method used is multiple linear regression analysis. The results of this study indicate that credit risk (NPL) and Capital (CAR) have no effect on stock prices, liquidity risk (LDR), market risk (NIM) and earnings (ROA) have a positive and significant effect on stock prices, while corporate governance has a negative and significant effect to stock prices. Keywords: Stock price, Credit risk, Liquidity risk, Market risk, Earnings and Capital